Clinical influences of anticentromere antibody on primary Sjögren’s syndrome in a prospective Korean cohort - Youngjae Park (The Korean Association of Internal Medicine, 2021)
Background/Aims This study was performed to clarify inf luences of anticentromere antibody (ACA) on clinical phenotypes of primary Sjögren’s syndrome (pSS) patients in Korea. Methods We assessed 318 patients who met the 2016 American College of Rheumatology/ European League Against Rheumatism classification criteria for pSS. All patients were selected from the Korean Initiative of primary Sjögren’s Syndrome (KISS), a prospective cohort. Among them, 53 patients were positive for ACA, while another 265 patients were not. We compared various clinical data including demographic features, extra-glandular manifestations (EGMs), clinical indices, and laboratory values available from the KISS database between the two groups. Results Patients in the ACA-positive pSS group were older (p = 0.042), and had higher xerostomia inventory scores (p = 0.040), whereas glandular dysfunction represented with Schirmer I test was more severe in the ACA-negative group. More frequent Raynaud’s phenomenon and liver involvement (both p < 0.001) and less articular involvement (p = 0.037) were observed among the EGMs in the ACA-positive group. Less frequency of leukopenia (p = 0.021), rheumatoid factor (p < 0.001), anti-Ro/SSA antibody positivity (p < 0.001), and hypergammaglobulinemia (p = 0.006), as well as higher positivity rates of anti-nuclear antibody and anti- topoisomerase antibody (p < 0.001 and p = 0.006, respectively) were found in the laboratory data in the ACA-positive pSS group. Conclusions Considering distinct phenotypes in hematological and serological features and EGMs, we should monitor the occurrence of these clinical features among pSS patients with ACA in caution.